(untitled) (Globalization and Business, 2023)
People believe that leadership is a way to improve their personal, professional, and social lives. That is why there has always been an interest in this phenomenon. Researchers have tried to find out what characteristics differentiate leaders from other people and what qualities make them successful. The qualities of a leader - intuition and the ability to see the future, the ability to motivate and encourage employees - occur especially during critical crisis situations. They need to be able to identify and solve problems in a timely manner, and ultimately lead the organization in the right direction. The current reality created by the coronavirus, the massive scale of the epidemic, and its unpredictability place great demands on leaders in their professional activities. As Vladimir Papava points out, it is true that the coronavirus by its very nature is primarily a medical problem, but it has created particular difficulties for the economy. In particular, in order to prevent the spread of the disease, it became necessary to minimize contact between people, which is why many firms had to stop operating (Papava, 2020). This sudden sequence of events, which develops rapidly, leads to a high degree of uncertainty, disorientation, and a sense of lost control, and exacerbates emotional disorder. In such a situation, in order to maintain the organizational environment, great importance is attached to the leader, his / her personal characteristics, and ability to lead the activity.The aim of the paper is to determine whether Covid-19 had the desired characteristics of leadership and determine whether the desired traits for leaders changed during the pandemic. To achieve this goal, it is necessary to solve the following tasks: to determine what importance is attached to the qualities of a leader in a pandemic, and to identify those traits that have become more important during a pandemic. The study identifies the challenges that leaders face because of the coronavirus. The analysis of these issues will help us to find the desired characteristics of a leader in the current reality and to develop recommendations for shaping the organizational environment in such a way that it is possible to implement effective leadership. The results obtained will be valuable as they will enable people to find in pandemic conditions the ability to develop characteristics that will help them succeed in their careers and personal lives. Managers will analyze the qualities that will help them not lose the trust and respect of employees in a crisis situation, and with the help of which they will be able to save and move the organization forward. According to Peter Drucker, the results of creative activities of entrepreneurs affect not only the economy, but also society (Bedianashvili, 2017: 11), so successful leaders can be considered the basis of successful business, successful economy and the success of the country. The reality created by the Covid pandemic has brought new demands on leaders. They should try to create a psychologically safe environment to enable employees to express their potential. In this new reality, leaders have a greater responsibility to protect employee well-being, ensure their involvement, and productivity, and create an appropriate environment for the generation of new ideas. Analysis of secondary data shows that the importance of resilience and compassion, and emotional intelligence, increased during the pandemic. This suggests that in times of crisis, great attention should be paid to understanding the feelings and opinions of employees, to establish a sincere relationship with them. The importance of effective communication has also increased. Expressing opinions openly and correctly became especially valuable for staff during a pandemic. The second important finding presented in the paper is the reduction of the importance of technical skills and authority. As it turned out, during the pandemic period, there was a shift from relatively rigorous skills to more humane, milder skills and competencies.